B value and first‐order motion moment optimized data acquisition for repeatable quantitative intravoxel incoherent motion DWI. Issue 6 (28th January 2022) - Simchick, Gregory; Geng, Ruiqi; Zhang, Yuxin; Hernando, Diego
Abstract : Purpose: To design a b value and first‐order motion moment (M1 ) optimized data acquisition for repeatable intravoxel incoherent motion (IVIM) quantification in the liver. Methods: Cramer‐Rao lower bound optimization was performed to determine optimal monopolar and optimal 2D samplings of the b ‐M1 space based on noise performance. Monte Carlo simulations were used to evaluate the bias and variability in estimates obtained using the proposed optimal samplings and conventional monopolar sampling. Diffusion MRI of the liver was performed in 10 volunteers using 3 IVIM acquisitions: conventional monopolar, optimized monopolar, and b‐ M1 ‐optimized gradient waveforms (designed based on the optimal 2D sampling). IVIM parameter maps of diffusion coefficient, perfusion fraction, and blood velocity SD were obtained using nonlinear least squares fitting. Noise performance (SDs), stability (outlier percentage), and test–retest or scan–rescan repeatability (intraclass correlation coefficients) were evaluated and compared across acquisitions. Results: Cramer‐Rao lower bound and Monte Carlo simulations demonstrated improved noise performance of the optimal 2D sampling in comparison to monopolar samplings. Evaluating the designed b‐ M1 ‐optimized waveforms in healthy volunteers, significant decreases ( p < 0.05) in the SDs and outlier percentages were observed for measurements of diffusion coefficient, perfusion fraction, and blood velocity SD in comparison to measurements obtained using monopolar samplings. Good‐to‐excellent repeatability (intraclass correlation coefficients ≥ 0.77) was observed for all 3 parameters in both the right and left liver lobes using the b‐ M1 ‐optimized waveforms. Conclusions: 2D b‐ M1 ‐optimized data acquisition enables repeatable IVIM quantification with improved noise performance. 2D acquisitions may advance the establishment of IVIM quantitative biomarkers for liver diseases.